Life estimation by varying the critical plane orientation in the modified Carpinteri-Spagnoli criterion - Camilla Ronchei; Andrea Carpinteri; Giovanni Fortese; Andrea Spagnoli; Sabrina Vantadori; Marta Kurek; Tadeusz ?agoda (Fracture and Structural Integrity)
The modified Carpinteri-Spagnoli (C-S) criterion is a multiaxial high-cycle fatigue criterion based on the critical plane approach. According to such a criterion, the orientation of the critical plane is linked to both the averaged directions of the principal stress axes and the fatigue properties of the material. The latter dependence is taken into account through a rotational angle, ?. Then, the multiaxial fatigue strength estimation is performed by computing an equivalent stress amplitude on the critical plane. In the present paper, some modifications of the original ? expression are implemented in the modified C-S criterion. More precisely, such modified expressions of ? depend on the ratio between the fatigue limit under fully reversed shear stress and that under fully reversed normal stress (in accordance with the original expression), and can be employed for metals ranging from mild to very hard fatigue behaviour. Some experimental data available in the literature are compared with the theoretical results in order to verify if the modified ?expressions are able to improve the fatigue strength estimation capability of the modified C-S criterion.